2021
DOI: 10.1002/admt.202101105
|View full text |Cite
|
Sign up to set email alerts
|

Compacted Laser‐Induced Graphene with Bamboo‐Like Carbon Nanotubes for Transformable Capacitive Energy Storage Electrodes

Abstract: Laser‐induced graphene (LIG) has drawn attention for energy storage devices owing to its fascinating material properties as well as for its use in the effective production of porous structures. However, the low packing density of LIG, which is caused by macroscopic voids owing to rapid degassing during the instantaneous photothermal process, limits the improvement of device performance. Herein, the fabrication of compacted LIG composite is introduced, wherein, the unused voids are filled with bamboo‐like carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Previous research on LIG has primarily centered around energy storage devices , and physical sensors . In these prior studies, LIG has been employed as an electrode or sensing material in electronic devices due to its substantial surface area and its sensitivity to strain.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on LIG has primarily centered around energy storage devices , and physical sensors . In these prior studies, LIG has been employed as an electrode or sensing material in electronic devices due to its substantial surface area and its sensitivity to strain.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with Figure 9 , it can be found that the in situ deposited CNTs filled the pores well at all porosities, while C-CBPs had a better filling effect for large pores above 150 nm but almost no filling effect at all for pores between 50 and 100 nm. This may be because, compared with I-CBPs, the CNTs inside C-CBPs may be due to agglomeration, which makes it difficult to fill the surface of EG particles and the tiny pores between EG, FG and resin, but a small number of MWCNTs were still dispersed during the preparation process, so they can play a similar filling role as I-CBPs for the pores between 0~50 nm [ 58 , 59 , 60 ]. Therefore, the pores between 0~50 nm can be filled similarly to I-CBPs, although the effect is not as good as that of I-CBPs.…”
Section: Resultsmentioning
confidence: 99%
“…So far, LIG in different substrates has been implemented in several devices, namely sensors, ,,, energy-storage devices, and conductive tracks for flexible circuits . The low sheet resistance and apparent porous/open structure of LIG produced in parylene suggest that it could be used for MSC fabrication.…”
Section: Resultsmentioning
confidence: 99%